Λαϊκός πολιτισμός στην ψηφιακή εποχή: παραμύθια και ηλεκτρονικά παίγνια - Rosy-Triantafyllia Angelaki (Syn-Thèses, 2022)
Fairy tales are timeless stories that introduce people to the literary, social and cultural heritage of diverse cultures and evolve to reflect contemporary social culture. Today, as the field of folklore studies expands and recognizes the contribution of the internet and virtual reality to the preservation, dissemination and creation of forms of folk culture, indigenous traditional stories and fairy tales are adapted for mainstream media platforms and enter into a complex media space in order to stimulate children's cultural literacy. The fairy tales, therefore, are not a simplified representation of reality but an engaging metaphorical convergence of symbols, diversity, social expectations, transformed into computer games. In this context, this article focuses on contemporary transformations of the Grimm brothers' folk tales, which are particularly popular and beloved by children and adults, into electronic role-playing, adventure and action games. Drawing on Children's Literature, Folklore, Game Design and Serious Games’ theories, this article examines the relationship between literature, folk culture and narrative and technology. We examine video games that are extensions of popular Grimm brothers' fairy tales and, particularly, the way in which folk narratives create new collectivities that chart a new course for the evolution of the folk tradition.